Difference means subtract, so we use subtraction:
*first we need to make the fractions have the same denominator
1/4 = 3/12
2/3 = 8/12
126(3/12) - 78(8/12)
*since the fraction in the first term is smaller than the second, make it improper
125(15/12) - 78(8/12)
now simply subtract:
125 - 78
= 47
15 - 8
= 7
* this is now (7/12)
now put them back together:
47(7/12)
That's the final answer!
Answer:
Answer B: 10.12
Step-by-step explanation:
Let the numbers be represented by a, b and c. Their sum is 44.84. The number a is 24.6. Further, assume that b = c.
Then 24.6 + b + b = 44.84.
Let's isolate 2b:
Subtract 24.6 from both sides of this equation, obtaining:
2b = 20.24.
Finally, divide both sides of this equation by 2. We get b = 10.12.
This corresponds with Answer B.
Answer:
10 is the answer
Step-by-step explanation:
thank me layer
Answer:
Step-by-step explanation:it’s up two and left 4 and do that equation 5 times